Pengaruh Komunikasi Electronic Word of Mouth dan Security terhadap Buying Interest melalui Trust Sebagai Variabel Intervening pada Online Shop Shopee (Studi Kasus Pada Mahasiswa UST Yogyakarta) - Serly Puspita Dewi (Program Studi Manajemen Fakultas Ekonomi UST, 2020)
The purpose of this study is 1) Test and determine the significance of the positive influence of Electronic Word of Mouth Communication (E-WOM) on Trust, 2) Test and know the significance of the positive influence of Security on Trust, 3) Test and know the significance of the positive influence of Electronic Word of Mouth Communication (E-WOM) on Buying Interest, 4) Testing and knowing the significance of the positive influence of Security on Buying Interest, 5) Testing and knowing the significance of the positive influence of Trust on Buying Interest, 6) Testing and knowing the significance of the positive influence of Electronic Communication Word of Mouth and Security on Trust, 7) Test and determine the significance of the positive influence of Electronic Word of Mouth Communication and Security on Buying Interest. This research belongs to the type of quantitative research. The study population was Shopee site users in UST Yogyakarta students. To determine the sample, researchers used a questionnaire. The research sample was obtained through a questionnaire distributed by researchers to respondents in the UST area of ​​Yogyakarta. The sample members used were 115 respondents. Data analysis techniques using data quality tests, descriptive statistics, classic assumption tests, multicollinearity tests, and multiple linear regression tests.